2021
DOI: 10.12928/pharmaciana.v11i1.17805
|View full text |Cite
|
Sign up to set email alerts
|

Formulation optimization and antioxidant test for Self-nano emulsifying drug delivery system of soursop leaves (Annona muricata L.) chloroform extract using candlenut oil as oil phase

Abstract: Soursop leaves (Annona muricata L.) chloroform extract has an anticancer agent that can be developed for traditional medicine preparation, even though the extract's solubility is low in the water. This study aims to generate new soursop leaves chloroform extract in the Self-Nano Emulsifying Drug Delivery System (SNEDDS). The expected result is that the solubility increases so that the drug delivery system is more effective. The extraction process of soursop leaves uses the percolation method with chloroform as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The results obtained from UV-Vis spectrophotometry are important factors in seeing the shape of the SEFs formula made and revealed that the transmittance value close to 99% indicates the clarity of an emulsion (Artanti et al, 2021). Measurement of transmittance (%T) used a wavelength of 650 nm.…”
Section: Transmittance Of Quercetin-sefs (R3)mentioning
confidence: 99%
“…The results obtained from UV-Vis spectrophotometry are important factors in seeing the shape of the SEFs formula made and revealed that the transmittance value close to 99% indicates the clarity of an emulsion (Artanti et al, 2021). Measurement of transmittance (%T) used a wavelength of 650 nm.…”
Section: Transmittance Of Quercetin-sefs (R3)mentioning
confidence: 99%